Analysis of Pressure Loss for Treatment Process of Demineralized Water at the Water Treatment Plant Unit at PT. ABC North Sumatra - Donda Donda; Darni Paranita; Dimas Frananta Simatupang (Justek : Jurnal Sains dan Teknologi, 2024)
Abstract: For the demineralized water treatment process, the water from the Portable Water Pound is pumped to the Reverse Osmosis system by a centrifugal pump. The pump provides the necessary force for the fluid to reach the Reverse Osmosis system. In a piping system, fluid flow in water treatment industries experiences pressure drop. The objective of this research is to determine the pressure loss and Reynolds number. The method includes calculating flow rate, Reynolds number, and pressure loss. The research results indicated that in a pipe diameter of 15 cm with a total pipe and fitting length of 5.0303 m, the average Reynolds number with an average fluid flow rate of 20.8 m3/hour was 61,411.46 (turbulent flow). Meanwhile, in a 10 cm diameter pipe with a total pipe and fitting length of 27.2228 m and the same average fluid flow rate, the Reynolds number was 86,671.40 (turbulent flow). The total pressure loss obtained at a temperature of 32°C is 323,382.68 Pa. The water flow rate has a positive relationship with the pressure loss in the pipe. The higher the flow rate, the greater the pressure loss. The Reynolds number also increases with the flow rate, indicating that higher flow rates result in higher Reynolds numbers and turbulence in the flow.Abstrak: Untuk proses pengolahan air demineral, air dari Portable Water Pound yang dipompakan menuju Reverse Osmosis membutuhkan tenaga yang diberikan oleh pompa. Pompa yang digunakan ialah pompa sentrifugal. Air yang dipompakan menuju Reverse Osmosis membutuhkan tekanan dari pompa sentrifugal tersebut agar fluida bisa sampai ke dalam Reverse Osmosis. Dalam suatu sistem perpipaan, aliran fluida dalam industri pengolahan air mengalami penurunan tekanan. Tujuan dari penelitian ini adalah untuk menentukan kehilangan tekanan dan bilangan Reynold. Metode yang digunakan meliputi perhitungan debit aliran, bilangan Reynolds, dan kehilangan tekanan. Hasil penelitian menunjukkan bahwa pada diameter pipa 15 cm dengan panjang pipa dan fitting 5,0303 m menghasilkan rata-rata bilangan Reynold dengan debit fluida rata-rata sebesar 20,8 m3/jam sebesar 61.411,46 (turbulensi). Sementara itu, pada diameter 10 cm dengan panjang pipa dan fitting 27,2228 m menghasilkan rata-rata bilangan Reynold dengan debit fluida yang sama sebesar 86.671,40 (turbulensi). Kehilangan tekanan total yang diperoleh pada suhu 32 0C adalah sebesar 323.382,68 Pa. Debit aliran air memiliki hubungan positif dengan kehilangan tekanan dalam pipa. Semakin tinggi debit aliran, semakin besar kehilangan tekanan yang terjadi. Bilangan Reynolds juga berbanding lurus dengan debit aliran, yang menunjukkan bahwa semakin besar debit aliran, semakin besar pula nilai Reynolds dan aliran akan mengalami turbulensi.